Surface profile of minority carrier lifetime in 65 and 100 MeV fluorine ion irradiated n-Si (111). (January 2017) - Shinde, N.S.; Dahiwale, S.S.; Deore, A.V.; Bhoraskar, V.N.; Dhole, S.D.
Abstract: Irradiation-induced modifications of excess minority carrier recombination time (lifetime) τ in CZ-grown crystalline n-Si (111) with resistivity 60 Ω cm are reported. Samples were irradiated with 65 and 100 MeV fluorine ions in the fluence range of 2×10 10 –10 14 ions/cm 2 . The surface and depth profile of lifetime was measured using photoconductive decay (PCD) technique. In the entire set of ion-irradiated samples, lifetime was found to decrease monotonously with increasing ion fluence. This decrease in lifetime is attributed to the electronic energy loss Se induced generation of carrier traps and vacancies. Moreover, the higher Se in 65 MeV energy fluorine ions is responsible for the rapid decrease in lifetime as compared to the 100 MeV ions. The excess Se in 65 MeV fluorine ions is consumed in defect production over the ion track as well as surface and sub-surface recrystallization, thus exhibiting Se dependence. The variation in the surface lifetime is associated to the competition between surface defects and Se dependent recrystallization. Almost complete recovery in the lifetime towards the pre-irradiation level after annealing at 750 °C for a period of 1 h, confirms that the lifetime modification is due to irradiation-induced carrier trapping centers. Highlights: Heavy fluorine ion irradiation was used to modify the minority carrier lifetime in c-Si. Lifetime profiling of irradiated n-Si were compared using LED based lifetime measurement system. Spatial and Depth distribution of defects over a volume are important for device performance.